Light Fe isotopes in arc magmas from cold subduction zones: Implications for serpentinite-derived fluids oxidized the sub-arc mantle - Chen, Zuxing; Chen, Jiubin; Tamehe, Landry Soh; Zhang, Yuxiang; Zeng, Zhigang; Zhang, Ting; Shuai, Wangcai; Yin, Xuebo (Geochimica et cosmochimica acta, 2023)
Arc basalts typically have higher Fe3+/ΣFe ratios but lighter Fe isotopic compositions than mid-ocean ridge basalts (MORB); however, the reasons for these differences are unclear. Here, we report new Fe isotope data for fresh lavas from the Mariana subduction zone, along with available Fe-B-Sr-Nd isotope and B/Nb ratio data for global arc basalts, to constrain the role of serpentinite dehydration in sub-arc mantle oxidation. The basaltic lavas from the Mariana Arc, like other arc basalts from cold subduction zones in the west Pacific, have lighter Fe isotope compositions (δ56Fe = 0.02 ± 0.02‰; 1SD; n = 9) than the MORB-like δ56Fe values of the middle Mariana Trough basalts (δ56Fe = 0.09 ± 0.02‰; 1SD; n = 8). Notably, the significant negative correlations between the δ56Fe values and the proxy for the addition of serpentinite-derived fluids (i.e., B isotopes and B/Nb ratios) indicate that the serpentinite-derived fluid contribution is a first-order control on the across-arc Fe isotope variations. Dehydration of subducted slab serpentinites or dragged-down forearc serpentinites at sub-arc depths can release isotopically light Fe fluids in the form of Fe2+–SOx complexes. Sulfate-rich fluids containing adequate Fe to metasomatize the sub-arc mantle can cause light Fe isotope compositions and high Fe3+/ΣFe ratios in arc basalts. Alternatively, the low δ56Fe values and high Fe3+/ΣFe ratios of arc magmas may be generated by direct melting of the mélange, which includes dragged-down sulfate-rich forearc serpentinites. Comparatively, serpentinite-derived components are absent at back-arc depths because of the earlier breakdown of serpentine minerals. Accordingly, the back-arc basin basalts exhibit MORB-like δ56Fe-δ11B values and B/Nb–Fe3+/ΣFe ratios. Therefore, the across-arc Fe isotope variations and the decoupling of Fe3+/ΣFe and δ56Fe in global arc magmas can be explained by the different contributions of subducted serpentinites.